The ability to appropriately distinguish throws for different target positions - Kusafuka, Ayane; Yamamoto, Rintaro; Okegawa, Taishi; Kudo, Kazutoshi (Frontiers in Sports and Active Living, 2023)
Repeated and accurate throwing of an object to a target position is a special human motor skill. It is particularly important to understand accuracy, which has received less attention than speed due to difficulties in measurement. Accuracy has been studied in terms of reducing errors against a single target, but also in terms of distinguishing appropriate throws for targets in different positions. In this study, this ability was investigated by evaluating the two-dimensional distributions of the pitch locations of 15 pitches to three target positions in university students with and without baseball experience. The center, major and minor axis length, major and minor axis ratio, slope, area, and percentage of overlapping area of the 95% confidence ellipse were compared between target positions and participants using a two-way repeated-measures analysis of variance (ANOVA). The center and area of the ellipse indicate the mean and variability of the error, respectively. The lengths of the major axes correspond to the variability of the release timing, and the minor axes correspond to the variability of the release point in space. Therefore, the ratio of the major and minor axes indicates how the variability of the pitching motion is controlled. The slope of the ellipse corresponds to the throwing arm's trajectory, and the percentage of overlap area means the ability to distinguish throws at different target positions. The result showed a main effect of participants on all indices except the center of the ellipse. This indicates that participants can generally distinguish throws by target positions regardless of their baseball experience, although participants with baseball experience may naturally reduce variability. Furthermore, participants with baseball experience demonstrated a decrease variability in release timing, which is a primary contributor to the pitch location variability, relative to the spatial variability of the pitching movements. This reduction in timing variability may be attributed to advanced motor control mechanisms.